"Mes que un club" and an empty Camp Nou : a case study of strategic ambiguity and Catalan nationalism at Football Club Barcelona - Kassing, Jeffrey W. (SAGE business cases, 2019)
Football Club Barcelona represents a successful modern sport entity with global influence and a celebrated past. It also has an undeniable connection to the region of Catalonia and has become in many ways a vehicle mobilized in the resurgent movement to seek Catalan independence from Spain. This case study considers how the strong and lasting link with Catalonia coupled with the club's strategically ambiguous "mes que un club" (more than a club) motto combined to place the club in the difficult position of deciding to play a game in an empty stadium. The action, intended to be symbolic, proved questionable given the assorted stakeholders affected by the decision.